Synthesis Of 2,5-Dimersapto-1,3,4-Thiadiazol Products - Jololiddinov Fazliddin Yuldashali Ugli; Xaitboev Xamid; Boboev Baxrom Nurillaevich (The American Journal of Applied Sciences, 2020)
Potentially bioactive 2,5-bis derivatives of 1,3,4-thiadiazole with alkaloid moieties were synthesized byreaction of 1,3,4-thiadiazol-2,5-dithiol with N-acryloyl-substituted derivatives of the alkaloids anabasine,cytisine, and D-pseudoephedrine.1,3,4-Thiadiazole-2,5-disulfonic acid was synthesized by oxidation of 2,5-dimercapto-1,3,4-thiadiazole,and onium salts of this acid were prepared by its reactions with selected alkaloids and secondaryamines.